How basic cognitive processing affects children's math problem-solving performance? - Chen, Xin; Wang, Yuhan; Liu, Kaichun; Zhang, Shuyuan; Yu, Xiao; Yang, Yang; Yang, Xiujie (Cognitive development, 2025)
Although previous research emphasizes the importance of domain-general cognitive abilities and domain-specific numerical knowledge in general mathematics domains (Geary, 2004), their roles in specific domain, especially word problem solving, remain underexplored. This study investigated the contributions of various cognitive components to early word-problem performance by adapting Geary’s (2004) cognitive competencies framework. Ninety-five Chinese kindergarten children (ages 3.39–6.55 years, mean age = 5.58, SD = 0.91) completed tasks assessing language processing, visuospatial processing, conceptual knowledge, procedural knowledge, and word problems. Results revealed that conceptual and procedural knowledge mediated the relationship between basic cognitive processing (language and visuospatial systems) and word problems. Specifically, phonological awareness in the language system showed an indirect association with word problems via procedural knowledge, and via a sequential pathway involving conceptual and procedural knowledge. No significant indirect effect of receptive vocabulary was found. Both aspects of the visuospatial system, visual perception and mental rotation, showed indirect associations with word problems via a sequential pathway involving conceptual and procedural knowledge. These results broaden Geary’s framework to encompass early word problem solving and provide initial guidance for future research concerning children who face mathematical learning difficulties. This includes the exploration of potential areas for screening and intervention. •Conceptual and procedural knowledge mediated the link between basic cognitive processing and word problems.•Phonological awareness was linked to word problems via procedural knowledge and a sequential conceptual–procedural pathway.•Visual perception and mental rotation were linked to word problems via sequential conceptual–procedural paths.